Phenotypic features of paroxysmal dyskinesia in Dachshund dogs: 62 cases (2017-2025) - Bethany Boyd; Giulia Corsini; Dakir Polidoro; Sofie F M Bhatti; Nicholas Grapes; Diego Alza; Luca Motta; Sara Formoso; Steven De Decker; Simon Bertram; Samantha Gilbert; Athina Karpozilou; et al. (Journal of Veterinary Internal Medicine, 2026)
Abstract Background Paroxysmal dyskinesia (PxD) has not been characterized in Dachshunds. Hypothesis/Objectives Describe the phenotype, treatment, and outcome of PxD in Dachshunds. Animals Sixty-two Dachshunds with presumptive PxD. Methods Observational, retrospective, multicenter study of dogs diagnosed with PxD between 2017 and 2025, with prospective information using an owner questionnaire. Results Median age at presentation was 3.2 years (range, 1-11 years). Episodes were characterized by shifting (55/62; 88.7%), single (4/62; 6.5%) limb or cervical dystonia (28/62; 45.2%), tremors (25/62; 40.3%), dystonic head tremors (15/62; 35.5%), truncal sway (20/62, 32.3%), kyphosis (17/62; 27.4%), and ataxia (15/62, 24.2%) or head sway (12/62, 19.4%). Shifting limb dystonia was exhibited in all (19/55; 34.5%), pelvic (7/55; 12.7%), or thoracic (1/55; 1.8 %) limbs. Ptyalism (25/62; 40.3%), vomiting (23/62; 37.1%), or lip smacking (25/62; 40.3%) were common. All dogs were diagnosed with presumptive idiopathic paroxysmal non-kinesigenic dyskinesia. Most common treatments were gluten-free diet (42/62; 67.7%), levetiracetam (9/62; 14.5%), phenobarbital (5/62; 8.1%), or no treatment (18/62; 29%). Follow-up was available for 49 of 62 (79%) dogs with a median follow-up of 543 days (range, 5-2903 days). Twenty-six of 49 (53%) dogs had a decrease, 19 of 49 (38.8%) had no change and 4 of 49 (8.2%) had an increase in the frequency or intensity of episodes. Conclusions and clinical importance Paroxysmal dyskinesia occurs in young Dachshunds. Shifting limb dystonia is a common feature, and it can affect the pelvic limbs exclusively, mimicking spinal cord disease. Most dogs experienced a decrease in numbers of events regardless of treatment.